2018
DOI: 10.1039/c7em00360a
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and evaluation of PUF-PAS sampling rates across the Global Atmospheric Passive Sampling (GAPS) network

Abstract: Passive air samplers equipped with polyurethane foam (PUF-PAS) are frequently used to measure persistent organic pollutants (POPs) in ambient air. Here we present and evaluate a method to determine sampling rates (R), and the effective sampling volume (V), for gas-phase chemical compounds captured by a PUF-PAS sampler deployed anywhere in the world. The method uses a mathematical model that requires only publicly available hourly meteorological data, physical-chemical properties of the target compound, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…However, prudence should be taken when environmental concentrations are calculated from the mass of the chemical collected from passive sampler devices. Fortunately, existing web-based and GUI mathematical models are available to back-calculate environmental concentrations from masses collected from passive sampling devices (Apell et al, 2016; Herkert et al, 2018; Tcaciuc et al, 2015; Thompson et al, 2015). Currently, water passive sampling media such as LDPE still needs to be spiked with DCs; for PUF-PAS, if the sampling location is not common, e.g., above water or the location presents unusual high wind speed (>10 m s −1 ), DCs should also be spiked to verify/calculate sampling rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prudence should be taken when environmental concentrations are calculated from the mass of the chemical collected from passive sampler devices. Fortunately, existing web-based and GUI mathematical models are available to back-calculate environmental concentrations from masses collected from passive sampling devices (Apell et al, 2016; Herkert et al, 2018; Tcaciuc et al, 2015; Thompson et al, 2015). Currently, water passive sampling media such as LDPE still needs to be spiked with DCs; for PUF-PAS, if the sampling location is not common, e.g., above water or the location presents unusual high wind speed (>10 m s −1 ), DCs should also be spiked to verify/calculate sampling rates.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of gas-phase PCB congeners were determined by dividing the mass of each congener collected in the PUF disk by the congener-specific effective sampling volume, as described in equation (1): CPCBi a=mPUF PCBi/Veff PCBi where C PCBi a is the gas-phase concentration for the i th PCB (ng m −3 ), m PUF PCBi is the mass of the i th PCB on the PUF (ng) and V eff PCBi is the effective sampling volume for the i th PCB (m 3 ). The effective sampling volumes were obtained from modeled and calculated sampling rates from local meteorology (Herkert et al, 2018) and the spiked depuration compounds. Sampling rates ranged from 2.9 to 8.4 m 3 d −1 , whereas congener specific sampling volumes ranged from 26 to 400 m 3 .…”
Section: Methodsmentioning
confidence: 99%
“…41 As previously discussed, direct comparison of active and passive sampling data requires conversion of passive-sampling concentrations from ng per PUF per d to ng m À3 using models. 27,42 However, we have previously shown that it is possible to calculate temporal trends directly from the primary ng per PUF per d concentrations 19,33 and therefore used the same methodology in this study. To compare the corresponding active and passive time series, we computed the value of each exponential trend at the middle point of their overlapping period.…”
Section: Temporal Trend Analysismentioning
confidence: 99%
“…It is, however, unlikely that the highly reactive nature of GOM allows it to pass through the pores of the diffusive barrier. The most recent modelling estimations suggest that the "effective lifetime" of GEM is around 6 months (Corbitt et al, 2011;Horowitz et al, 2017). The atmospheric lifetime of GOM due to reduction and deposition is on the order of days to weeks (Ariya et al, 2015;Horowitz et al, 2017;Shah et al, 2016).…”
Section: Passive Air Samplingmentioning
confidence: 99%
“…The most recent modelling estimations suggest that the "effective lifetime" of GEM is around 6 months (Corbitt et al, 2011;Horowitz et al, 2017). The atmospheric lifetime of GOM due to reduction and deposition is on the order of days to weeks (Ariya et al, 2015;Horowitz et al, 2017;Shah et al, 2016). Although uncertainties remain, the shorter atmospheric lifetime and higher deposition fluxes of GOM translate to GEM making up the majority of TGM in most places (typically > 95 %; Cole et al, 2014;Driscoll et al, 2013;Rutter et al, 2009;Slemr et al, 2015).…”
Section: Passive Air Samplingmentioning
confidence: 99%